THE CARBON CAPTURE AND SEQUESTRATION: TECHNOLOGY OVERVIEW - S. Pirzada, M. D.; Pirzada, F. N. (The Nucleus, 2020)
Carbon capture and sequestration (CCS) technologies remove carbon dioxide from flue gases. It is then stored instead of being released into the atmosphere. CCS has the potential to mitigate global warming by capturing carbon dioxide (CO2) at its major production centres such as fossil fuel power plants. Large scale capture of CO2has already been achieved commercially. The CCS is technically feasible and fairly well developed but to date no large-scale power plant is being operated with a full carbon capture and storage system. Compared to a plant without CCS, one with CCS can cut CO2 emissions to the atmosphere by approximately 80-90%. However, the energy required to accomplish CCS increases the fuel needs of a coal-fired plant by about 25%. This, combined with the total system costs significantly increases the cost of energy. This makes CSS currently a relatively expensive mitigation option. Still if fossil fuels remain a major part of the energy mix, the global exigency to reduce carbon dioxide emissions laid under Kyoto protocol can make CCS an attractive option. This article discusses the possibilities and limitations of CCS. The technical and economic uncertainties and obstacles in the implementation of CCS have been illustrated. The status of industrial-scale storage projects in operation and those in the pipeline has also been reviewed.